Smart Methodology of Stiffness Nonlinearity Identification Vibration System - M. S. M., Sani; Ouyang, H.; Cooper, J.E.; Che Ku Eddy Nizwan, Che Ku Husin (2013)
Nonlinear identification is a very popular topic in the area of structural dynamics. Detection, localisation and quantification of nonlinearities are very important steps for assessing faults or damages in engineering structures. There have been many studies of identifying structural nonlinearities based on vibration data but most methods are only suitable for a small number of degrees of freedom and few nonlinear terms. In this paper, a procedure that utilises the restoring force surface method is developed in order to identify the parameters of nonlinear properties such as cubic stiffness, bilinear stiffness or free play. This method employs measured vibration data, and can be applied to structures of many degrees-of-freedom. In this paper, NASTRAN is used to compute the frequencies and modes of the structure under study. The simulated nonlinear model is formulated in modal space with additional terms representing nonlinear behaviour. Nonlinear curve fitting then enables interpretation of the nonlinear stiffness via the restoring force surface. The method is shown by MATLAB simulations to yield quite accurate identification of stiffness nonlinearity.